Patient acceptable symptom state in scleroderma: results from the tocilizumab compared with placebo trial in active diffuse cutaneous systemic sclerosis. (25th October 2017) - Arnold, Michael B; Khanna, Dinesh; Denton, Christopher P; van Laar, Jacob M; Frech, Tracy M; Anderson, Marina E; Baron, Murray; Chung, Lorinda; Fierlbeck, Gerhard; Lakshminarayanan, Santhanam; Allanore, Yannick; Riemekasten, Gabriela; et al.
Abstract: Objectives: Patient acceptable symptom state (PASS) as an absolute state of well-being has shown promise as an outcome measure in many rheumatologic conditions. We aimed to assess whether PASS may be effective in active diffuse cutaneous SSc differentiating active from placebo. Methods: Data from the phase 2 Safety and Efficacy of Subcutaneous Tocilizumab in Adults with Systemic Sclerosis (faSScinate) trial were used, which compared tocilizumab (TCZ) vs placebo over 48 weeks followed by an open-label TCZ period to 96 weeks. Three different types of PASS questions were evaluated at weeks 8, 24, 48 and 96, including if a current state would be acceptable over time as a yes vs no response and Likert scales about how acceptable a current state is if remaining over time. Additional outcomes assessed included modified Rodnan skin score, HAQ disability index (HAQ-DI), physician and patient global assessments on a visual analogue scale, CRP and ESR. Results: The placebo group consisted of 44 patients and the TCZ group had 43 patients. At baseline, 33% achieved a PASS for all three PASS questions, with the proportion increasing to 69, 71 and 78%, respectively, at 96 weeks. Changes in PASS scores showed a moderately negative correlation with HAQ-DI and patient and physician global assessments visual analogue scales, which indicates expected improvements as PASS improved. The PASS question, 'Considering all of the ways your scleroderma has affected you, how acceptable would you rate your level of symptoms?' showed significant correlations with patient-reported outcomes and differentiating placebo vs TCZ at 48 weeks ( P = 0.023). Conclusion: PASS may be used as a patient-centred outcome in SSc, especially as a 7-point Likert scale. Further validation is required to determine the utility as an outcome measure in trials and clinical practice.